THE TECHNOLOGY OF PRODUCING THIN THREE-LAYER SHRINK FILM OF THE MODIFIED POLYETHYLENE WITH COMPLEX ADJUSTABLE OPERATING CHARACTERISTICS AND HIGH ADAPTABILITY - Alexandra Vladimirovna Kuzmina; Galina Mikhaylovna Danilova-Volkovskaya (Современная наука и инновации)
The article presents research the characteristics of the film based on recycled polyethylene and modified polyethylene for production of thin-layer shrinkable film with improved process ability and performance. The article presents results modified polyethylene composition and results of optimization of the production technology of multilayer packaging films.